2022
DOI: 10.1371/journal.pone.0264462
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Human Immunodeficiency Virus treatment and family and social influence as barriers to accessing HIV care services in Belu, Indonesia

Abstract: Access to HIV care services, including antiretroviral therapy (ART), is essential for improving health outcomes of people living with HIV (PLHIV) and reducing HIV transmission and AIDS-related deaths. As a part of a qualitative study in Belu, this paper describes the use of traditional medicines for HIV treatment and family and social influence as barriers to access to HIV care services among PLHIV. One-on-one in-depth interviews were employed to collect data from 46 PLHIV (26 women and 20 men) and 10 healthca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The most significant difference is in the access to HIV care services, with most PLHIV in Yogyakarta accessing HIV care services or ART, while only about 25% in Belu accessing ART [ 40 , 41 ]. Yogyakarta and Belu were selected as the study settings because of feasibility, familiarity and the potential of undertaking the current study successfully as we have conducted several studies on HIV topics in these settings[ 17 , 42 , 43 ]. The two settings were also selected because they have different characteristics, which enabled us to make comparisons between urban and rural, good and limited HIV services, good and limited transportation systems, etc., and understand how those characteristics contribute to influencing the participants’ QoL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant difference is in the access to HIV care services, with most PLHIV in Yogyakarta accessing HIV care services or ART, while only about 25% in Belu accessing ART [ 40 , 41 ]. Yogyakarta and Belu were selected as the study settings because of feasibility, familiarity and the potential of undertaking the current study successfully as we have conducted several studies on HIV topics in these settings[ 17 , 42 , 43 ]. The two settings were also selected because they have different characteristics, which enabled us to make comparisons between urban and rural, good and limited HIV services, good and limited transportation systems, etc., and understand how those characteristics contribute to influencing the participants’ QoL.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have also reported several factors associated with a lower level of QoL of PLHIV, including social factors such as stigma and discrimination [ 13 , 14 ], non-disclosure of HIV status [ 15 ] and poor access to healthcare services [ 16 , 17 ]. Rather than being discrete negative factors, social determinants may be intertwined within the lives of PLHIV, making their impact even worse in terms of QoL.…”
Section: Introductionmentioning
confidence: 99%
“…These accessibility dimensions were reflected in the fact that participants could afford to buy herbal medicines at public markets or via online sources, or were able to make traditional medicines themselves out of roots, leaves and bark of plants that they could easily find, or via care sought from local traditional healers. Although there have never been studies exploring the influence of packaged herbal medicines and traditional medicines on the access of MLHIV to HIV care services or treatment, some previous studies involving people living with HIV (PLHIV) in general have suggested that the use of traditional medicines has influenced adherence to ART [ 51 , 52 , 53 , 54 , 55 ]. Our findings also suggest that peer influence played an important role in the use of these packaged herbal and traditional medicines by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Such poor environmental conditions were seen by participants as causing difficulties in their access to HIV care services and dissatisfaction towards the management of their HIV-related health conditions [10,48]. It is plausible to suggest that such conditions or limitations could have also been the barriers that impede access to ART by the majority of PLHIV in the district [17,22]. These poor environmental conditions or limitations can be categorised as system-level barriers to access to HIV care services, as highlighted in previous findings in other settings [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported several factors associated with a lower level of QoL of PLHIV, including social factors such as stigma and discrimination [13,14], nondisclosure of HIV status [15] and poor access to healthcare services [16,17]. Rather than being discrete negative factors, social determinants may be intertwined within the lives of PLHIV, making their impact even worse in terms of QoL.…”
Section: Introductionmentioning
confidence: 99%